2006
DOI: 10.1111/j.1834-7819.2006.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion uptake into demineralized dentine from glass ionomer cement following pretreatment with silver fluoride and potassium iodide

Abstract: Background: Diamine silver fluoride (Ag(NH 3 ) 2 F), referred to as AgF, has been shown to provide a pronounced antimicrobial action against caries. The clinical application of this material has been limited by the staining associated with both teeth and tooth coloured restorative materials. The application of potassium iodide (KI) after AgF eliminates stain formation. The purpose of this study was to determine if a prior application of silver fluoride and potassium iodine to demineralized dentine affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 11 publications
2
33
0
2
Order By: Relevance
“…Knight et al reported strontium incorporation into dentine by applying FVII 44) . Interest in the release of strontium from modern glass ionomer materials have been increased 45) .…”
Section: Discussionmentioning
confidence: 99%
“…Knight et al reported strontium incorporation into dentine by applying FVII 44) . Interest in the release of strontium from modern glass ionomer materials have been increased 45) .…”
Section: Discussionmentioning
confidence: 99%
“…The staining of carious dentin can be minimized by the application of potassium iodide solution after treatment without reducing the effect (Knight et al, 2006). Diammine silver fluoride has been shown to arrest caries in animal models (Tanzer et al, 2010) and to be more effective than sodium fluoride varnish in human trials (Chu et al, 2002;Llodra et al, 2005;Rosenblatt et al, 2009;Tan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…11 The electron probe microanalysis technique (EPMA) has confirmed the transfer of strontium and fluoride ions into the dentine from glass ionomer cement. [12][13][14] The ability to measure the percentage weights of chosen elements enables an analysis of the amount of tooth loss, the penetration depth of reaction products and their affects upon tooth demineralization.…”
Section: Introductionmentioning
confidence: 99%